2013
DOI: 10.1111/lam.12031
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of sodium nitrite with high-pressure treatments on the inactivation of Escherichia coli BW25113 and Listeria monocytogenes NCTC 11994

Abstract: Significance and Impact of the Study: High hydrostatic pressure (HHP) is an effective nonthermal food preservation technology that can be used to increase food safety and shelf life with minimal changes in food quality. Various antimicrobial agents including bacteriocins, lysozyme, chitosan, lactoperoxidase and essential oils have been tested in combination with HHP to enhance the effect of mild-pressure treatments. This is the first report of a synergistic bactericidal effect of high pressure and acidified ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Brandt et al (2011) found significant inhibition of L. monocytogenes after combined treatment with acidic calcium sulphate and octanoic acid. Moreover, the effect of sodium nitrite with high hydrostatic pressure against e. coli BW25113 and L. monocytogenes NCTC 11994 showed a synergistic reduction of bacterial count at pH 4.0 (Alba et al 2013).…”
Section: Prevention Of Contamination In Foodmentioning
confidence: 95%
“…Brandt et al (2011) found significant inhibition of L. monocytogenes after combined treatment with acidic calcium sulphate and octanoic acid. Moreover, the effect of sodium nitrite with high hydrostatic pressure against e. coli BW25113 and L. monocytogenes NCTC 11994 showed a synergistic reduction of bacterial count at pH 4.0 (Alba et al 2013).…”
Section: Prevention Of Contamination In Foodmentioning
confidence: 95%
“…It was also proposed that the protection of salts may be correlated with the degree of electrostriction of water, for example, salts of lower electrostriction effect, NaCl and KCl, have less bactericidal effects on pressure‐treated S. aureus and E. coli when compared to salts of larger electrostriction effect Na 2 SO 4 and CaCl 2 (Gayán et al., 2013). The bactericidal effect of high pressure was enhanced by nitrite in S. aureus and E. coli ; mechanisms of which may be related to the disability against nitrosamine or oxidative stress but are still unclear which need more studies in the future (De Alba, Bravo, Medina, Park, & Mackey, 2013b; Duranton, Guillou, Simonin, Chéret, & de Lamballerie, 2012; Jofré et al., 2010). Moreover, high‐pressure sublethal E. coli was shown to be sensitive to bile salts in the recovery medium, but the effect was reversible as the resistance of cells can be regained after incubation in trypticase soy agar (Chilton, Isaacs, Manas, & Mackey, 2001).…”
Section: High Pressure Combined With Antimicrobial Hurdlesmentioning
confidence: 99%
“…The isostatic pressures applied to the foods are transferred immediately and are equally distributed; therefore, the treatment is not determined by the form or the extent of the food product [137]. Since the pressure is uniform, the shape is not affected and there is no clear breaking result on the packaging of foods [138]. The pressure is then spread for a fixed time interval, commonly a few seconds but sometimes up to 20 minutes.…”
Section: Hhp Processing Technologymentioning
confidence: 99%